Professional Development Activities of IELTS Trainers from Non-English Major - Wulandari, Nur Setyo; Yudi Cahyono, Bambang; El Khoiri, Niamika (Universitas Pendidikan Ganesha, 2021)
Professional development activities are done by English teachers from formal educational institutions and by trainers from non-English majors who teach IELTS preparation program in non-formal educational institutions. This study investigated the professional development activities done by IELTS trainers from non-English majors and how the professional development activities help them improve their teaching competencies. A case study design was applied, and an in-depth interview and documentary analysis were used to gain the data. Four selected research subjects were involved in this study. The results showed that the IELTS trainers' professional development activities include collaborative and independent learning activities. Furthermore, those activities help the IELTS trainers from non-English majors positively as they can fulfill their demand to improve their teaching competencies since there is limited institutional support for them in professional development. Therefore, the institution where the IELTS trainers work should provide adequate formal learning supports. In addition, the IELTS trainers in this study and other IELTS trainers should be involved in other informal learning activities more frequently.